Deflation in Japan - The Underlying Causes and its Ramifications - Blair, Rachel; Štěrbová, Ludmila, 1957-; Müller, David, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This thesis seeks to analyze deflation in Japan, which has been a persistent problem for more than two decades. This paper will provide a detailed explanation of what deflation is, and how it manifests itself in an economy. It will furthermore examine deflation's root causes and the warning signs that presented themselves just prior to the beginning of the deflationary period. From this point on the paper will examine the detrimental effects of deflation in Japan which became apparent after the 1989 crash in stock and asset prices, and it will analyze the actions the Bank of Japan took in the early days of deflation. The thesis will also examine quantitative easing, the unconventional monetary policy that the Bank of Japan implemented in 2001. Quantitative easing will be explained in detail, and moreover, it will be determine whether this form of monetary policy was successful at defeating Japan's persistent deflation. This paper will lastly analyze Japan's position in the 2008 global recession, and reveal why Japan experienced such devastating effects due to this financial crisis. It will then present "Abenomic's 2.0", the current economic policy being implemented in Japan. Lastly, the thesis will provide a prospective outlook on the economic future of Japan, and it will also reiterate the importance of analyzing Japan's ongoing battle with deflation and the lessons that can be learnt from their struggles.
Vedoucí práce: Ludmila Štěrbová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses